Vaginal candidosis: the place of butоconazol in pharmacotherapy - G S Bogdanova; Z S Zaidieva; V A Zayakin (IP Berlin A.V., 2013)
Vaginal candidosis is very common disease. To assess butоconazol therapeutical efficacy in treatment of chronic vaginal candidosis 58 patients in age of 22-48 years were examined. Inclusion criteria were: presence of history of 4 or more episodes of vaginal candidosis in an year, absence of sexually transmitted infections at the moment of examination. All patients were assigned to butоconazol (Ginofort) for vaginal administration. The results demonstrated high clinical and microbiological efficacy of butоconazol in chronic vaginal candidosis treatment.